Can the Profitability of Medical Enterprises Be Improved After Joining China's Centralized Drug Procurement? A Difference-in-Difference Design - Hua, Yu-Fei; Lu, Jin; Bai, Bing; Zhao, Han-Qing (Frontiers in Public Health, 2022)
This paper explores the impact of joining centralized drug procurement of China on the profitability of medical enterprises by the difference-in-difference (DID) model. When centralized procurement cannot bring enough cost savings to enterprises, the price competition caused by centralized procurement will lead to the decline of enterprise profits. In the short term, the negative impact of China's drug centralized procurement policy on the net profit of enterprises is not obvious in the year when enterprises win the bid. After the government officially purchases from pharmaceutical enterprises, the negative impact of the drug centralized procurement policy of China on the net profit of enterprises begins to appear gradually. Therefore, the generic drug manufacturers increase R&D investment and have their own heavy products of original drugs as soon as possible to enhance their core competitiveness.